ANALISIS HUBUNGAN ANEMIA DENGAN KEJADIAN ABORTUS DI RSUD SUKADANA TAHUN 2022 - Deviani Utami (Yayasan Pendidikan Medika Indonesia, 2022)
Abortion is the end of a pregnancy (by certain consequences) at or before the pregnancy is 22 weeks old or the fruit of the pregnancy has not been able to live outside the womb. Complications that occur during childbirth are the main cause of death in infants who were originally alive at the time the labor process began, but were later stillborn.This study aims to determine the relationship between anemia and the incidence of abortion in Sukadana Hospital in 2022.This type of research is analytical research. The research design used was cross sectional. The sampling technique in this study used a total of 41 people who met the inclusion criteria.It is known that most of the respondents aged 20-30 years as many as 40 (97.6%) were analyzed by chi square test with a p value of 0.09, 17 patients were found to be anemic (41.5%), 19 patients had abortions (46.3%). Based on the analysis and discussion above, it shows that there is a relationship between anemia and the incidence of abortion in Sukadana Hospital 2022.